2016
DOI: 10.1161/jaha.115.002813
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Costs Related to Lead Damage Occurring Within the First Year After a Cardiac Implantable Electronic Device Replacement Procedure

Abstract: BackgroundInadvertent damage to leads for transvenous pacemakers, implantable cardioverter‐defibrillators, and cardiac resynchronization therapy defibrillators is an important complication associated with generator‐replacement procedures. We sought to estimate the incidence and costs associated with transvenous lead damage following cardiac implantable electronic device replacement.Methods and ResultsUsing the Truven Health Analytics MarketScan Commercial Research Database, we identified health care claims bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
(33 reference statements)
1
22
0
Order By: Relevance
“…By 1993 it was estimated that the failure of polyurethane pacemaker leads alone would result in above $55 million dollars for device replacement [8]. A more recent 2016 study found that for pacemaker/defibrillator lead damage within the first year of device implantation results in approximately $1.1 billion costs, with damage to the leads occurring in 0.47% to 1.94% of implanted devices, depending on specific application [9]. In a smaller case study, 27 pacemaker leads were returned to the manufacturer and analyzed, with 8 of the devices having undergone material failure that lead to 4 high voltage failures and one death, with an average implantation time of approximately of 25.5 months [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By 1993 it was estimated that the failure of polyurethane pacemaker leads alone would result in above $55 million dollars for device replacement [8]. A more recent 2016 study found that for pacemaker/defibrillator lead damage within the first year of device implantation results in approximately $1.1 billion costs, with damage to the leads occurring in 0.47% to 1.94% of implanted devices, depending on specific application [9]. In a smaller case study, 27 pacemaker leads were returned to the manufacturer and analyzed, with 8 of the devices having undergone material failure that lead to 4 high voltage failures and one death, with an average implantation time of approximately of 25.5 months [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a smaller case study, 27 pacemaker leads were returned to the manufacturer and analyzed, with 8 of the devices having undergone material failure that lead to 4 high voltage failures and one death, with an average implantation time of approximately of 25.5 months [10]. Based upon the study being performed and the device selected for analysis, this failure rate may range from 0.47% over two and half years to 2.71% per year or higher [9,10]. Failures for commercially available medical devices result in patient morbidity and mortality, and a major cause of this is the lack of analysis that is performed prior to implantation of the devices [110].…”
Section: Introductionmentioning
confidence: 99%
“…In the study, damage to the electrodes was found, which was the cause of the exchange of the device in 0.46% of cases after pacemaker implantation, in 1.27% of cases after cardioverter implantation, and in 1.94 % of cases after implantation of the resynchronisation device. In each case, the complications were associated with costly hospitalisation [24]. Regional single-centre studies also confirmed the usefulness of the determination of BNP peptide, high-sensitivity troponin T, and LAVI in the evaluation of patients who had undergone permanent pacemaker implantation [25].…”
Section: Discussionmentioning
confidence: 71%
“…The longevity of cardiac implantable electronic devices (CIEDs) should be an important if not the primary performance attribute in model choice, as battery depletion is the dominant cause of device replacement, which entails not only fiscal cost but also risk of infection and lead failure . The longevities quoted by manufacturers for their latest generation of device models are inevitably projections (typically based on nonuniform settings) and have historically turned out to be overestimates in clinical practice, even after correction for use conditions .…”
Section: Introductionmentioning
confidence: 99%